A comparison of conventional and advanced 3D imaging techniques for percutaneous left atrial appendage closure - Heidari, Houtan; Kanschik, Dominika; Maier, Oliver; Wolff, Georg; Brockmeyer, Maximilian; Masyuk, Maryna; Bruno, Raphael Romano; Polzin, Amin; Erkens, Ralf; Antoch, Gerald; Reinartz, Sebastian Daniel; Werner, Nikos; et al. (Frontiers in Cardiovascular Medicine, 2024)
Background Understanding complex cardiac anatomy is essential for percutaneous left atrial appendage (LAA) closure. Conventional multi-slice computed tomography (MSCT) and transesophageal echocardiography (TEE) are now supported by advanced 3D printing and virtual reality (VR) techniques for three-dimensional visualization of volumetric data sets. This study aimed to investigate their added value for LAA closure procedures. Methods Ten patients scheduled for interventional LAA closure were evaluated with MSCT and TEE. Patient-specific 3D printings and VR models were fabricated based on MSCT data. Ten cardiologists then comparatively assessed LAA anatomy and its procedure relevant surrounding structures with all four imaging modalities and rated their procedural utility on a 5-point Likert scale questionnaire (from 1 = strongly agree to 5 = strongly disagree). Results Device sizing was rated highest in MSCT (MSCT: 1.90.8; TEE: 2.60.9; 3D printing: 2.51.0; VR: 2.51.1; p <0.01); TEE, VR, and 3D printing were superior in the visualization of the Fossa ovalis compared to MSCT (MSCT: 3.31.4; TEE: 2.21.3; 3D printing: 2.21.4; VR: 1.91.3; all p <0.01). The major strength of VR and 3D printing techniques was a superior depth perception (VR: 1.60.5; 3D printing: 1.80.4; TEE: 2.90.7; MSCT: 2.60.8; p < 0.01). The visualization of extracardiac structures was rated less accurate in TEE than MSCT (TEE: 2.60.9; MSCT: 1.90.8, p <0. 01). However, 3D printing and VR insufficiently visualized extracardiac structures in the present study. Conclusion: A true 3D visualization in VR or 3D printing provides an additional value in the evaluation of the LAA for the planning of percutaneous closure. In particular, the superior perception of depth was seen as a strength of a 3D visualization. This may contribute to a better overall understanding of the anatomy. Clinical studies are needed to evaluate whether a more comprehensive understanding through advanced multimodal imaging of patient-specific anatomy using VR may translate into improved procedural outcomes.